Kegiatan Agronomis untuk Meningkatkan Potensi Lahan Lebak menjadi Sumber Pangan - Zainal Ridho Djafar (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
Agronomical Activities to Increase the Potential of the Swampy Land To Be Food Sources.Â  Swampy land is potentially large enough to increase the production of food crops and holticulture. Out of the land area of about 13.2 milion hectares, only about 5 percent has been used intensively. The main problems in land use is the water system and soil fertility. Agronomic activities that can be done to improve the productivity of the land, among others, are improving the water system control, soil amelioration, cropping patterns and use of improved varieties. These activities can increase the production of food crops and holticulture. These activities should be carried out by considering environmental sustainability.